Outcomes of Limb‐Sparing Surgery Using Two Generations of Metal Endoprosthesis in 45 Dogs With Distal Radial Osteosarcoma. A Veterinary Society of Surgical Oncology Retrospective Study. Issue 1 (January 2016) - Mitchell, Katherine E.; Boston, Sarah E.; Kung, Marvin; Dry, Sarah; Straw, Rod C.; Ehrhart, Nicole P.; Ryan, Stewart D.
Abstract : Objective: To report outcomes in dogs with distal radial osteosarcoma (OSA) treated with metal endoprosthesis limb‐sparing surgery and compare outcomes between 2 generations of endoprosthesis. Study Design: Multi‐institutional retrospective case series. Animals: Forty‐five dogs with distal radial OSA treated with endoprosthesis and chemotherapy. Methods: Data of dogs treated with either first‐generation endoprosthesis (GEN1) or second‐generation endoprosthesis (GEN2) were sourced from medical records and radiographs. Surgical outcomes included postoperative lameness assessment and the presence, severity, and time to onset of complications. Oncologic outcomes included presence of local recurrence or metastasis, time to onset of local recurrence, metastasis‐free interval (MFI), and survival time. Results for surgical and oncologic outcomes were compared between GEN1 and GEN2. Results: Twenty‐eight dogs received GEN1 and 17 dogs received GEN2. There were 39 complications (96%, 14 minor, 29 major) including infection (78%), implant‐related complication (36%), and local recurrence (24%). Metastatic frequency was 67% and median MFI was 188 days (95% confidence interval [CI]: 126–250 days). Survival time ranged from 34 days to 6.1 years with a median of 289 days (95% CI: 207–371 days). There was no significant difference in complication severity, frequency, time to complication, MFI, or survival time between dogs receiving GEN1 and GEN2. Conclusion: There was no significant difference in outcomes between dogs receiving GEN1 and GEN2 for limb‐sparing surgery of the radius. Metastatic frequency and survival time for metal endoprosthesis were similar to that of amputation with curative intent chemotherapy.